SUBORDINASI PENGELOLAAN ZAKAT OLEH MASYARAKAT DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Nur Fadhilah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
Judicial review of the Law No 23 Year 2011 on Zakat‟s Management has been approved by the Constitutional Court on 31 October 2013. The Court decision No 86/PUU-X/2012 acknowledge the position of LAZ asan assistance of BAZNAS. Thus, LAZ as an institution founded by society is merely a subordinate.